AN APPRAISAL ON THE CONTRIBUTION OF MUSLIM WOMEN IN JUDICIARY IN NORTH-WEST NIGERIA - Barmo, Shafa'atu Aliyu; Tsoho, Aisha Abubakar (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This study examines the significant contributions of Muslim women in the judiciary of Northwest Nigeria, focusing on their roles, challenges, and impact on promoting gender equality and justice within the legal system. The research highlights the growing participation of Muslim women in both administrative and adjudicatory roles across Shari'ah and conventional courts. Despite the historical male dominance in the legal profession, Muslim women have made notable strides, particularly in regions where Shari'ah law is integrated with common law. Through qualitative research, including interviews with women in judicial positions, the study reveals that their involvement enhances inclusivity, diversity, and access to justice. It underscores the importance of increasing Muslim women's participation in the judiciary to foster gender-sensitive legal frameworks and inspire future generations of women to pursue careers in law. Additionally, the paper calls for further research into the long-term effects of Muslim women's contributions on the legal system and society at large.